Water Ecosystem Services : A Global Perspective - Martin-Ortega, Julia; Ferrier, Robert C.; Gordon, Iain J.; Khan, Shahbaz (Cambridge : Cambridge University Press, 2015)
This comprehensive volume describes how ecosystem services-based approaches can assist in addressing major global and regional water challenges, such as climate change, biodiversity loss, and water security in the developing world, by integrating scientific knowledge from different disciplines, such as hydrological modelling, environmental economics, psychology and international law. Empirical assessments at the national, catchment and regional levels are used to critically appraise this systemic approach, and the merits and potential limitations are presented. The practicalities of this approach with regard to water resources management, nature conservation, and sustainable business practices are discussed, and the role of society in underpinning the concept of ecosystem services is explored. Presenting new insights and perspectives on how to shape future strategies, this contributory volume is a valuable reference for researchers, academics, students and policy makers, in environmental studies, hydrology, water resource management, ecology, environmental law, policy and economics, and conservation biology.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Ecohydrology; Ecosystem services